2000
DOI: 10.1111/1467-6494.t01-1-00094
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality: Description, Measurement, and Relation to the Five Factor Model of Personality

Abstract: The present article focused on the development and measurement of a factor model of the expressions of spirituality. Study 1 (N = 534) involved the use of factor analysis to examine the latent factor structure in a sample of 11 measures of spiritual constructs. Study 2 (N = 938) focused on the replication of Study 1 results and on the construction and initial validation of an instrument to operationalize the factor model of spirituality. Results indicate that at least 5 robust dimensions of spirituality underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
304
1
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(339 citation statements)
references
References 48 publications
19
304
1
15
Order By: Relevance
“…Egan et al, 1999). Finally, Openness to experience, characterized by receptiveness to new ideas, approaches, and experiences (McCrae & Costa, 1997), was also fairly consistently shown to correlate with general paranormal belief (Egan et al, 1999;MacDonald, 2000;Smith et al, 2009). However, as with all other dimensions, the diverse measures of both personality and paranormal beliefs used, along with a small number of studies conducted, make it impossible to conclusively determine the relevance of this personality dimension in explaining and predicting paranormal beliefs.…”
Section: Origins Of Paranormal Beliefs and The Role Of Personalitymentioning
confidence: 91%
See 2 more Smart Citations
“…Egan et al, 1999). Finally, Openness to experience, characterized by receptiveness to new ideas, approaches, and experiences (McCrae & Costa, 1997), was also fairly consistently shown to correlate with general paranormal belief (Egan et al, 1999;MacDonald, 2000;Smith et al, 2009). However, as with all other dimensions, the diverse measures of both personality and paranormal beliefs used, along with a small number of studies conducted, make it impossible to conclusively determine the relevance of this personality dimension in explaining and predicting paranormal beliefs.…”
Section: Origins Of Paranormal Beliefs and The Role Of Personalitymentioning
confidence: 91%
“…Despite the majority of confirming studies, some nevertheless found no relationship between Neuroticism and paranormal beliefs (e.g. MacDonald, 2000;Tobacyk, 1982). It is also worth noting that Neuroticism is one of the dimensions of the Five Factor model most consistently related to religiosity (Saroglou, 2002;Saroglou & Jaspard, 2000).…”
Section: Origins Of Paranormal Beliefs and The Role Of Personalitymentioning
confidence: 96%
See 1 more Smart Citation
“…MacDonald (2000) points out that, except in cases in which spirituality emphasizes only personal experience and does not imply commitment and social practice (Belzen (2005) explains the difference), spirituality can exert influence on religiosity and promote help behavior, solidarity, and tolerance.…”
mentioning
confidence: 99%
“…In a second study with 938 undergraduate students (675 women, 263 men) with a mean age of 21.0 years (SD = 4.3 years), he used factor and reliability analyses to refine the model and develop a 98-item Expressions of Spirituality Inventory with good psychometric properties (MacDonald, LeClair, Holland, Alter, & Friedman, 1995;MacDonald, 1997MacDonald, , 2000. Through this process MacDonald has identified five dimensions of spirituality that are measured by the scales of the Expressions of Spirituality Inventory.…”
mentioning
confidence: 99%